Understanding ecosystems of the future will require more than realistic climate change experiments – A response to Korell et al. (30th October 2019) - De Boeck, Hans J.; Bloor, Juliette M. G.; Aerts, Rien; Bahn, Michael; Beier, Claus; Emmett, Bridget A.; Estiarte, Marc; Grünzweig, José M.; Halbritter, Aud H.; Holub, Petr; Jentsch, Anke; Klem, Karel; et al.
Abstract : This article is a response to Korell et al., 26, 325–327 ; See also the Commentary on this article by Muller et al., 26, e4–e5 ; See also the response to this Letter to the Editor by Korell et al., 26, 328–329 .